Community treatment orders and social outcomes for patients with psychosis: a 48-month follow-up study. - Vergunst, F; Rugkåsa, J; Koshiaris, C; Simon, J; Burns, T (Springer, 2017)
Purpose Community treatment orders (CTOs) are widely used internationally despite a lack of evidence supporting their effectiveness. Most effectiveness studies are relatively short (12-months or less) and focus on clinical symptoms and service data, while a little attention is given to patients’ social outcomes and broader welfare. We tested the association between the duration of CTO intervention and patients’ long-term social outcomes. Methods A sub-sample (n = 114) of community-based patients from the Oxford Community Treatment Order Evaluation Trial (OCTET) were interviewed 48 months after randomisation. Multivariate regression models were used to examine the association between the duration of the CTO intervention and social outcomes as measured by the social network schedule, Objective Social Outcomes Index, Euro-Qol EQ-5D-3L (EQ-5D), and Oxford Capabilities Questionnaire for Mental Health. Results No significant association was found between the duration of CTO intervention and social network size (IRR = 0.996, p = .63), objective social outcomes (B = -0.003, p = .77), health-related quality of life (B = 0.001, p = .77), and capabilities (B = 0.046, p = .41). There were no between-group differences in social outcomes when outcomes were stratified by original arm of randomisation. Patients had a mean of 10.2 (SD = 5.9) contacts in their social networks, 42% of whom were relatives. Conclusions CTO duration was not associated with improvements in patients’ social outcomes even over the long term. This study adds to growing concerns about CTO effectiveness and the justification for their continued use.